Landscape Approaches to Climate Change, Economics and Pandemics – Rethinking Calgary Parks and Open Space Systems - Sandalack A. Beverly (Lodz University of Technology Press, 2023)
Parks and open spaces are planned and designed to respond to the needs, issues and demographics of their time, but may not be the ‘right’ spaces or systems to address new populations or concerns. The City of Calgary’s Climate Resilience Strategy focuses on reducing greenhouse gas emissions and taking actions to mitigate the impact of extreme weather events. It is quiet on the subject of parks and open space systems and the potential of the landscape to help in addressing climate change. An approach is proposed that could bring together the languages and methods of landscape ecology, urban morphology and urban design. A landscape architecture studio took on this topic and the approach, with the study area consisting of one quadrant of Calgary that was developed in the 1950s–1980s. The methods included mapping and analysis (historic evolution, natural environment, urban structure, socio-demographics and the public realm) and synthesizing them in order to identify issues and formulate proposals. New spatial organizations and morphologies along with better ways of planning and designing landscape systems could help address issues of climate change and lead to the development of a more responsive public realm. This approach could also help to re-frame the city image.
Keywords: park systems; park and open space types; landscape architecture studio; combined methods; interdisciplinary framework; systemy parkowe; typy parków i przestrzeni otwartych; pracownia architektury krajobrazu; metody kombinowane; ramy interdyscyplinarne